EFFECT OF POLYA’S STRATEGY USING METHODS OF HOMOGENEOUS AND HETEROGENEOUS SMALL GROUPS ON LEARNING SOME BASIC VOLLEYBALL SKILLS - Ali Abdul-Hussein Hammoud Saleh (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. The development of effective learning strategies is essential in physical education, particularly in team sports such as volleyball, where acquiring fundamental skills requires structured instruction and active participation. Traditional teaching approaches often focus on repetition, which may not fully engage students or cater to their diverse learning needs. Therefore, it becomes important to explore innovative strategies that combine cognitive problem-solving with collaborative learning. Objectives. This study aimed to investigate the effect of Polya’s strategy, applied through homogeneous and heterogeneous small group methods, on learning some basic volleyball skills among intermediate school students. Method. The research employed an experimental method due to its appropriateness for the nature of the problem. The sample consisted of 54 students from the second intermediate grade at Al-Suwaira Intermediate School for Boys, divided into three classes of 18 students each. Two groups were taught using Polya’s strategy with different small-group structures—homogeneous and heterogeneous—while the third group served as a control. Data were analyzed using appropriate statistical procedures to determine the effectiveness of the applied methods. Results. The results showed that students who learned through Polya’s strategy in both homogeneous and heterogeneous groups significantly outperformed the control group in acquiring basic volleyball skills. The positive effect was attributed to the structured steps of Polya’s strategy, which encouraged systematic thinking, problem-solving, and active collaboration. Moreover, grouping methods provided opportunities for peer interaction and learning based on students’ styles and abilities. Conclusion. Polya’s strategy proved to be an effective instructional approach for enhancing skill acquisition in volleyball. This research contributes to the field of physical education by demonstrating the value of integrating cognitive strategies with group-based learning methods, offering practical implications for sports educators seeking to improve teaching effectiveness and student outcomes.